Reflections on the Impact of Urban Sprawl on the Architecture of the City: Lessons from Benin City, Nigeria - Odeyale, Timothy Oluseyi (Forum Geografi, 2023)
This paper focuses on Benin City, Nigeria, as a case study to explore urban sprawl and its associated problems resulting from unplanned and uncontrolled spatial expansion. Informal settlements house approximately 45% of Nigeria's urban population, leading to a range of land and environmental challenges. The study investigates how sustainable development goals can be realized through efficient sustainable planning and urban design concepts, with a focus on managing urban sprawl in the city. The methodology comprises a literature review, field investigation of unplanned or squatter settlements in a selected part of Benin City through the administration of 201 questionnaires, and an analysis of its developments and physical transformations. Understanding the issues of urban sprawl arising from the rapid spatial expansion of Benin City is crucial for achieving a well-organized, planned, orderly, and sustainable environment. This paper provides valuable insights and information to facilitate effective urban planning in the study area. Additionally, it offers guidance to practitioners and developers on the adoption of sustainability measures in their projects. The findings of this study contribute to expanding the knowledge horizon and serve as a reference for further research on spatial expansion and the incidence of sprawl in urban centers throughout Nigeria.